2011
DOI: 10.1109/tce.2011.6131132
|View full text |Cite
|
Sign up to set email alerts
|

Interoperability framework for smart home systems

Abstract: Recent advancements in smart home systems have increased the utilization of consumer devices and appliances in home environment. However, many of these devices and appliances exhibit certain degree of heterogeneity and do not adapt towards joint execution of operation. Hence, it is rather difficult to perform interoperation especially to realize desired services preferred by home users. In this paper, we propose a new intelligent interoperability framework for smart home systems execution as well as coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Some of the major issues were argued i.e., interoperability of heterogeneous devices in smart homes by using web techniques, energy saving mechanisms, real time response employ to energy awareness. In the article [43] authors proposed a novel intelligent interoperability framework aimed at smart homes. The proposed methodology grounded on SOAP simple object Access Protocol which aims to offer platform for heterogeneous devices for interoperation.…”
Section: Syntactic Interoperabilitymentioning
confidence: 99%
“…Some of the major issues were argued i.e., interoperability of heterogeneous devices in smart homes by using web techniques, energy saving mechanisms, real time response employ to energy awareness. In the article [43] authors proposed a novel intelligent interoperability framework aimed at smart homes. The proposed methodology grounded on SOAP simple object Access Protocol which aims to offer platform for heterogeneous devices for interoperation.…”
Section: Syntactic Interoperabilitymentioning
confidence: 99%
“…Their work focuses on the use of SOAP for interoperability and uses an Event-Condition-Action (ECA) mechanism for machine-2-machine interactions and orchestration of the devices. The SOAP-based interoperability framework has been further extended by Perumal et al [10] with the addition of a service stub to facilitate the addition of new devices and a database module to handle the queries of the SOAP messages (including home service functions, operation logic and access to other local or remote databases).…”
Section: Service-oriented Architectures (Soas)mentioning
confidence: 99%
“…The future improvements have been identified, including affordability with low cost technologies as well as information security and privacy issues, etc. Perumal proposed the interoperability framework for smart home systems in [4]. They indicated that the smart home system contains different devices, like home automation, cameras, fire alarms, energy management appliances.…”
Section: Literature Reviewmentioning
confidence: 99%